Water effect on the morphology and magnetic properties of poly(3-hexylthiophene) - de Paula, Fernando (International Journal of Scientific Research and Management (IJSRM), 2021)
Poly(3-hexylthiophene) magnetics characteristics and morphologic prepared in acetonitrile solution by electrochemical techniques have been studied, and the results are reported. The results indicate that the films prepared in small amounts of water in the electrolyte solution show significantly different morphology and magnetic behavior. The differences in these properties are explained in terms of different functional groups introduced during polymers film preparation.